P664 Association between pharmacologic loss of response profile of anti-TNF and clinical outcome with vedolizumab. (16th January 2018) - Berthaux, J; DeBoissieu, P; Amiot, A; Vaysse, T; Carbonnel, F; Collins, M
Abstract: Background: Patients with inflammatory bowel diseases (IBD) frequently respond and, subsequently loose response to anti-TNF. Loss of response (LOR) to anti-TNF can be either pharmacodynamics (PD) (adequate trough levels), or pharmacokinetic (PK) (low trough levels with or without immunisation). Vedolizumab is often prescribed in patients who have lost response to anti TNF, particularly in those with PD LOR. However, it is unknown as to whether response to vedolizumab is higher in patients with PD LOR to anti-TNF. The aim of this study was to assess the association between the pharmacologic profile of anti-TNF at the moment of LOR and clinical outcome with vedolizumab. Methods: In this retrospective cohort, we included all the consecutive IBD patients who received vedolizumab, and had anti TNF trough level at the moment of LOR, between June 2014 and December 2016. We assessed clinical remission, steroid-free remission and clinical benefit (defined by maintenance of Vedolizumab treatment and physician global assessment of clinical response) at week 14 and 52. We analysed the clinical benefit using Kaplan–Meier survival analysis, and predictive factors with logistic regression. Results: Sixty-two patients were included, among whom 29 (46%) had Crohn's disease. At vedolizumab initiation, 33 of 62 (53%) patients had a PK-LOR and 29 of 62 (46%) had a PD-LOR to anti-TNF. At week 14, the rates of clinical benefit, clinical remission, and steroid-free remission were 49 of 62 (79.0%), 33 of 62 (53.2%), and 24 of 62 (38.7%), respectively. At week 52, clinical benefit was 34 of 59 (57.6%). In multivariate analysis, there was a positive association between clinical benefit and ulcerative colitis (OR = 6.95, IC 95 [1.36–35.6], p = 0.02), PD-LOR (OR = 5.54, IC95 [1.03–28.74], p = 0.045), as well as multiple exposures to anti-TNFs (OR = 8.52, IC 95 [1.32–55.09], p = 0.03). No factor was associated with steroid-free remission at week 14, nor with clinical benefit at week 52. Conclusions: High trough levels of anti-TNF therapy at LOR appear to be associated with short-term but not with long-term benefit of vedolizumab. These results suggest that Vedolizumab can be prescribed to IBD patients who have lost response to anti-TNF, regardless of trough levels.